Leadership - Marian Iszatt-White and Christopher Saunders (New York, NY Oxford University Press, 2020)
Written by an author team from one of Europe's leading management schools, Leadership encourages critical appraisal of the mainstream viewpoints and personal reflection on leadership experience in a way that is both clear and highly engaging.
Includes bibliographical references and index
Keywords: Leadership